(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2020)
Despite the popularity of loyalty programs, evidence on the effects of rewards on consumer behavior is inconsistent. Behavioral loyalty is important for a company as it represents a consumer’s tendency to purchase on a regular basis. The goal of this paper is to explore the differences in behavioral patterns between loyalty program members who redeem coupons at till (redeemers) and those who do not (non-redeemers). A survey was carried out using a sample of 750 loyalty cards obtained from a national retail chain. The results show that coupons at till, as a monetary reward, reduced the time between purchases and increased the volume of purchases and average expenditure.